Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1007/s12325-021-02010-3
|View full text |Cite
|
Sign up to set email alerts
|

Cost of End-of-Life Inpatient Encounters in Patients with Chronic Kidney Disease in the United States: A Report from the DISCOVER CKD Retrospective Cohort

Abstract: Introduction Real-world data reporting healthcare resource utilisation and costs associated with end-of-life care for patients with chronic kidney disease (CKD) are limited. We examined length of hospitalisation and costs associated with end-of-life inpatient encounters using retrospective data from DISCOVER CKD. Methods Data on inpatient encounters for patients with CKD aged ≥ 18 years between January 2016 and March 2020 were extracted from the US Premier Hospital Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Nine studies were included which reported the costs of palliative care in hospital settings (Hanson et al, 2008; Isenberg et al, 2017; Kerr et al, 2017; McCarthy et al, 2015; Nathaniel et al, 2015; Pollock et al, 2022; Schneider et al, 2020; Sellars et al, 2019; Tan & Jatoi, 2011). With regards to quality as assessed by the JBI critical appraisal checklist for economic evaluations, n=2 were deemed to be of high quality (McCarthy et al, 2015; Sellars et al, 2019), n=6 were of moderate quality (Isenberg et al, 2017; Kerr et al, 2017; Nathaniel et al, 2015; Pollock et al, 2022; Schneider et al, 2020; Tan & Jatoi, 2011), and n=1 of low quality (Hanson et al, 2008). Most of these studies (n=6) were from the USA, and there were also studies from Australia (Sellars et al, 2019), the Netherlands (Schneider et al, 2020) and the UK (Kerr et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies were included which reported the costs of palliative care in hospital settings (Hanson et al, 2008; Isenberg et al, 2017; Kerr et al, 2017; McCarthy et al, 2015; Nathaniel et al, 2015; Pollock et al, 2022; Schneider et al, 2020; Sellars et al, 2019; Tan & Jatoi, 2011). With regards to quality as assessed by the JBI critical appraisal checklist for economic evaluations, n=2 were deemed to be of high quality (McCarthy et al, 2015; Sellars et al, 2019), n=6 were of moderate quality (Isenberg et al, 2017; Kerr et al, 2017; Nathaniel et al, 2015; Pollock et al, 2022; Schneider et al, 2020; Tan & Jatoi, 2011), and n=1 of low quality (Hanson et al, 2008). Most of these studies (n=6) were from the USA, and there were also studies from Australia (Sellars et al, 2019), the Netherlands (Schneider et al, 2020) and the UK (Kerr et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…DISCOVER CKD (http://clinicaltrials.gov identifier: NCT04034992) is a hybrid, multinational, observational cohort study of individuals with CKD 16 . The study aims to provide contemporary real‐world insights to inform clinical practice and improve understanding of the epidemiology, and clinical and economic burden of CKD 16–18 . The aim of this analysis was to describe the treatment pathways for key glucose‐lowering therapies in individuals with CKD and T2D, using data from two databases within the DISCOVER CKD retrospective cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the analyses of the entire dataset of chronic conditions (output found in Table B), significant relationships at p < .0001 were found between residential status most predictor variables, with the following exceptions: gender (both male and female) and age group (0-17). These significances largely held in the subset of data in the hospitalization dataset with only CKD, COPD, and obesity patients (output in Table C), except that age (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) was not significant at p = 0.0035 and payor (Medicare) p = 0.0031; gender remained insignificant.…”
Section: Table 2 Hospitalization Dataset Sociodemographic Outcomes By...mentioning
confidence: 94%
“…28 The median total direct cost of IP care was $431 USD; dialysis was found to be the most expensive component, followed by ward costs, and lastly pharmaceutical costs. 29 This cost-related research is not of high interest due to the socioeconomics of Nigeria versus the United States and the types of healthcare system employed by either (FFS vs. governmentbased); however, what is interesting is the discussion in this article of rural patients. Due to societal inequity and a high percentage of the rural population being impoverished, most rural citizens do not qualify for the government-based insurance, National Health Insurance Scheme (NHIS); even if rural patients were able to enroll in the scheme, the NHIS only covers six renal care sessions per year and does not cover all commonly deemed necessary services.…”
Section: Pollock Et Al (mentioning
confidence: 99%
See 1 more Smart Citation